The use of tranquilizer compounds in wintering rations for steers. - Koch, B.A.; Smith, E.F.; Richardson, D.; McCartor, M.M. (Kansas Agricultural Experiment Station, 2011)
Recent experimental work with chemical tranquilizers has indicated that these substances may be of value in the fattening ration of beef cattle under certain conditions. Theoretically at least, the chemical tranquilizers should calm the animals and thus reduce the amount of energy lost due to nervousness and unnecessary muscular activity. It is also possible that they have some other effect upon the animal which leads to increased weight gains and improved feed efficiency. The trial reported herein• was designed to determine whether or not tranquilizer compounds will improve the performance of beef cattle on a wintering ration.
Keywords: Beef; Tranquilizer compounds; Rations; Feed efficiency